Malawi Economic Monitor, May 2016 : Absorbing Shocks, Building Resilience - World Bank (World Bank, Lilongwe, Malawi, 2016)
This report consists of two parts: Part 1 presents a review of recent economic developments and a macroeconomic outlook. Part 2 focuses in greater depth on a special, selected topic relevant to Malawi's development prospects. This report focuses on agricultural risk management. Malawi is now set to suffer a second year of poor harvests due to the effects of a drought that is sweeping Southern Africa. This drought has had a serious impact both on the economy and on food security, requiring a major humanitarian response. The current situation underscores Malawi's serious need to improve the resilience of the agricultural sector and to develop a better system of risk management. With the country expected to continue to face climate-induced shocks into the future, it is vital that the Government considers how best to mitigate the impact of such shocks. In 2015 Malawi recorded a GDP growth rate of just 2.8 percent, with this low rate the result of both adverse weather conditions and macroeconomic instability. Flooding in southern districts followed by a countrywide drought resulted in a contraction in agricultural production. Maize, the key crop in terms of food security, recorded a 30.2 percent year-on-year drop in production. As a result, an estimated 2.8 million people (17 percent of the population) were unable to meet their 2015/16 food requirements.